Pile fabric and method for producing same
By using poly(3-hydroxyalkanoate) fibers and high-softening point fibers and undergoing hot pressing treatment, the problem that the fleece cloth in the prior art does not have ocean decomposition and hardening of the touch is solved, and the ocean decomposition, soft feel and hair suppression effect is achieved.
Patent Information
- Application Number
- CN202380062293.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-29
- Filing Date
- 2023-08-10
- Publication Date
- 2025-05-02
AI Technical Summary
The polylactic acid of the existing stuffed fabric does not have marine decomposition properties, and when the hair is shed is prevented from falling out through the backing treatment, the touch of the stuffed part becomes harder and the ground tissue becomes harder.
Poly(3-hydroxyalkanoate) fibers are used as the pile fibers and are wound with fibers with a softening point higher than the fibers. Part of the fibers are melted and bonded by hot pressing treatment, controlling the bending rigidity of the structure and the length change rate of the pile fibers.
The marine decomposition of the fleece fabric is achieved, the soft feel and softness of the fleece are maintained, while suppressing hair loss.
Smart Images

Figure CN119923496A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a biodegradable pile fabric and a method for producing the same. Background Art
[0002] Synthetic fibers made of synthetic resins such as polyethylene terephthalate have been widely used as pile fibers. In recent years, from the perspective of environmental protection, research on the use of biodegradable resins that decompose in the natural environment is being conducted. For example, Patent Document 1 describes a biodegradable carpet that uses biodegradable fibers formed of biodegradable polymers with aliphatic polyesters such as polylactic acid as the main component as pile fibers. In addition, Patent Document 2 describes a pile fabric in which the pile yarn is formed of filament yarns containing aliphatic polyester fibers with L-lactic acid and / or R-lactic acid as the main component.
[0003] On the other hand, in the case of pile fabric, the linting is generally prevented by backing treatment. In addition, Patent Document 3 describes that in a pile fabric using acrylic fiber, the linting is prevented by thermocompression bonding the pile fabric from the back side.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2002-248047
[0007] Patent Document 2: Japanese Patent Application Publication No. 2002-004151
[0008] Patent Document 3: International Publication No. 2011-055455 Summary of the invention
[0009] Problems to be solved by the invention
[0010] However, the polylactic acid used in the pile fabrics described in Patent Documents 1 and 2 is not marine degradable, and further improvement is required from the viewpoint of environmental protection.
[0011] In addition, when the pile fabric is treated with a backing to prevent linting, the pile fibers of the pile portion may shrink and fuse, which may harden the touch and give a rough feel. In addition, when the pile fabric is heat-pressed from the back side as in Patent Document 3, the ground structure of the pile fabric becomes hard, and the pile fabric may become hard.
[0012] In order to solve the above-mentioned conventional problems, the present invention provides a pile fabric having marine decomposability, good pile feel, excellent softness, and suppressed lint shedding, and a method for producing the same.
[0013] Solution to the problem
[0014] One or more embodiments of the present invention relate to a pile fabric comprising a ground structure and pile fibers entangled with a ground yarn constituting the ground structure and raised on a surface of the ground structure, wherein the pile fibers comprise poly(3-hydroxyalkanoate) fibers, the ground yarn comprises fibers having a higher softening point than the poly(3-hydroxyalkanoate) fibers, and in the pile fibers entangled with the ground yarn, at least a portion of the poly(3-hydroxyalkanoate) fibers present on a back side of the ground yarn are fused, and when the pile fabric is heat-treated for 15 minutes in a dry hot gas atmosphere at 140° C. without a load, the change rate of the length of the pile fibers before and after the heat treatment is 15.0 to 40.0%, and the bending rigidity of the ground structure of the pile fabric is 1.00×10 -4 N·m 2 / m or less.
[0015] One or more embodiments of the present invention relate to a method for producing a pile fabric, the method comprising: a step of producing the pile fabric, the pile fabric comprising a ground structure and pile fibers entangled with a ground yarn constituting the ground structure and raised on a surface of the ground structure; and a step of subjecting the pile fabric to a thermal compression bonding treatment from a back side, the pile fibers comprising poly(3-hydroxyalkanoate)-based fibers, the ground yarn comprising fibers having a higher softening point than the poly(3-hydroxyalkanoate)-based fibers, the temperature conditions of the thermal compression bonding treatment being: (1) above the softening point of the poly(3-hydroxyalkanoate) type fiber and below the melting point of the poly(3-hydroxyalkanoate) type fiber +10°C, and (2) below the softening point of the fibers in the ground yarn that have a softening point higher than the poly(3-hydroxyalkanoate) type fiber, the method not including a polishing step, or in the case of including a polishing step, the polishing is carried out at a temperature above the glass transition temperature of the poly(3-hydroxyalkanoate) type fiber and below the softening point of the poly(3-hydroxyalkanoate) type fiber -40°C.
[0016] Effects of the Invention
[0017] The present invention can provide a pile fabric which has marine decomposability, a good pile feel, excellent softness, and suppressed lint loss.
[0018] According to the production method of the present invention, a pile fabric which has marine decomposability, a good texture of pile, excellent softness, and suppressed lint loss can be preferably obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram of an example of a pile fabric.
[0020] Figure 2This is a production process diagram schematically showing a step of subjecting a pile fabric to a thermal compression bonding treatment at a given temperature from the back side.
[0021] Figure 3 This is a schematic cross-sectional view for explaining a method for evaluating the softness of a pile fabric.
[0022] Figure 4 This is a schematic cross-sectional view for explaining a method for evaluating the softness of a pile fabric.
[0023] Figure 5 This is a photograph showing the surface of the pile portion of an example of a pile cloth in which the pile tips are not fused.
[0024] Figure 6 This is a photograph showing an example of the pile surface of a pile fabric in which the pile tips are fused together.
[0025] Figure 7 This is an overview of the method for measuring the length of pile fibers.
[0026] Explanation of symbols
[0027] 1.19 Pile fabric
[0028] 2 Ground yarn
[0029] 3 Pile head
[0030] 4 Pile Fiber
[0031] 5. Melt bonding
[0032] 6 The top of the earth organization
[0033] 7 The top of the pile fibers
[0034] 8 Distance (pile height)
[0035] 9 The front end of the pile fiber
[0036] 10 Processing equipment
[0037] 11 Heating roller
[0038] 12 Cooling rubber roller
[0039] 13, 14 Metal cooling roller
[0040] 15 Guide roller
[0041] 16, 17 Container
[0042] 18 Pile fabric raw material rolls
[0043] 18a Pile fabric raw material roll surface
[0044] 18b Back side of pile fabric raw material roll
[0045] 21 Grey fabric of pile fabric
[0046] 22 Horizontal Platform
[0047] 31 The tangent line drawn at the front end of the grey fabric piece of pile fabric
[0048] 41 Upper part of pile fiber
[0049] 51 Distance (length of pile fibers) DETAILED DESCRIPTION
[0050] The present inventors have conducted intensive research to solve the above-mentioned problems. As a result, it was found that, for a pile fabric comprising a ground structure and pile fibers entangled with a ground yarn constituting the ground structure and raised on the surface of the ground structure, the following (1) to (4) can be used to impart marine decomposability to the pile fabric, improve the feel of the pile portion and the softness of the ground structure, and suppress linting: (1) poly(3-hydroxyalkanoate)-based fibers (hereinafter also referred to as "P3HA-based fibers") are used as pile fibers; (2) a ground yarn comprising fibers having a higher softening point than the poly(3-hydroxyalkanoate)-based fibers is used in the ground yarn, and at least a portion of the poly(3-hydroxyalkanoate)-based fibers present on the back side of the ground yarn among the pile fibers entangled with the ground yarn is melt-bonded; (3) the pile fibers in the pile fabric are placed in a state where the dry heat shrinkage rate at 140°C satisfies a given range of residual shrinkage; and (4) the bending rigidity of the ground structure in the pile fabric is set within a given range.
[0051] Although poly(3-hydroxyalkanoate) (hereinafter also referred to as "P3HA") is marine degradable, it has low heat resistance and shrinks significantly at a temperature of about 100° C. On the other hand, in the case of pile fabrics, in order to prevent the pile fibers from falling off (linting), a backing treatment is performed, that is, a process in which an adhesive is applied to the back of the pile fabric and heated to a temperature of 100° C. or higher (for example, 130° C.) by a tenter to dry and solidify the adhesive. However, when P3HA-based fibers are used as pile fibers, the P3HA-based fibers shrink significantly due to heat in the tenter process, and the touch becomes hard, and the pile fabric tends to have a rough feel. The present inventors have found that, by subjecting the pile fabric to a heat-compression bonding treatment from the back side of the ground structure without backing treatment, and by causing at least a portion of the P3HA-based fibers present on the back side of the ground yarn to melt-bond in the pile fibers entangled with the ground yarn, the P3HA-based fibers raised on the surface of the ground structure are not melt-bonded, thereby suppressing the lint shedding, maintaining the soft feel of the pile portion, and maintaining the softness of the ground structure well, wherein the specific temperature conditions are: (1) above the softening point of the poly(3-hydroxyalkanoate)-based fibers and below the melting point of the poly(3-hydroxyalkanoate)-based fibers +10° C., and (2) below the softening point of the fibers in the ground yarn that are higher than the poly(3-hydroxyalkanoate)-based fibers. In addition, polishing may not be included when manufacturing the pile fabric, and in the case of a polishing step, the soft feel of the pile portion can be maintained by performing polishing under specific temperature conditions.
[0052] In this specification, when a numerical range is represented by "to", the numerical range includes the values at both ends (upper limit and lower limit). For example, a numerical range such as "X to Y" is a range including the values at both ends such as X and Y. In addition, in this specification, when multiple numerical ranges are described, the numerical range is a combination of the upper limits and lower limits of different numerical ranges.
[0053] In this specification, biodegradability refers to the property of being decomposed to the molecular level by the action of microorganisms and eventually becoming water and carbon dioxide, and marine decomposability refers to the property of being decomposed to the molecular level by the action of microorganisms in the ocean and eventually becoming water and carbon dioxide. Poly(3-hydroxyalkanoate) has been widely used as a biodegradable bioplastic with marine decomposability. By using P3HA-based fibers as pile fibers, excellent marine decomposability can be imparted to pile fabrics.
[0054] In this specification, the biodegradability of pile fabrics varies depending on aerobic or anaerobic conditions, water system or solid phase system, microbial community, temperature, etc., and can be specifically measured based on any one of ISO14851, ISO14852, ISO17556, ISO14855, ISO14855-2, ISO14853 and ISO15985. In addition, the biodegradability based on microorganisms in seawater can be evaluated by the BOD (Biochemical Oxygen Demand) test method using oxygen consumption.
[0055] (Pile Fiber)
[0056] In one or more embodiments of the present invention, the pile fibers include P3HA fibers. From the viewpoint of marine decomposability, when the total amount of the pile fibers is set to 100% by weight, it is preferred that the P3HA fibers include 80% by weight or more, more preferably 90% by weight or more, further preferably 95% by weight or more, and particularly preferably 100% by weight of P3HA fibers. The pile fibers may include other fibers as needed within the scope that does not impair the effects of the present invention. As other fibers, preferably biodegradable biodegradable fibers may be used, and synthetic fibers, natural fibers, and regenerated fibers containing aliphatic polyesters other than P3HA may be used. As aliphatic polyesters other than P3HA, for example: polylactic acid, polycaprolactone, polybutylene adipate terephthalate, polybutylene succinate adipate, and polybutylene succinate may be cited. As natural fibers, natural cellulose fibers and natural animal fibers may be cited. Examples of natural cellulose fibers include cotton fibers, kapok fibers, flax fibers, hemp fibers, ramie fibers, jute fibers, Manila fibers, and kenaf fibers. Examples of natural animal fibers include wool fibers, mohair fibers, cashmere fibers, camel fibers, alpaca fibers, and angora fibers. Examples of regenerated fibers include regenerated cellulose fibers such as rayon and regenerated protein fibers such as regenerated collagen fibers.
[0057] In one or more embodiments of the present invention, "P3HA-based fibers" refer to fibers containing 80% by weight or more of P3HA, preferably 85% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more. In one or more embodiments of the present invention, the P3HA-based fibers can be composed of 100% by weight of P3HA as needed.
[0058] As P3HA, a resin having a 3-hydroxyalkanoate repeating unit can be used. Specifically, a resin having a 3-hydroxyalkanoate repeating unit represented by the following general formula (1) can be used.
[0059] [Chemical formula 1]
[0060]
[0061] In the general formula (1), R 1 represents an alkyl group having 1 to 15 carbon atoms, preferably an alkyl group having 1 to 10 carbon atoms, and more preferably an alkyl group having 1 to 8 carbon atoms. The alkyl group may be linear or branched. 1 Examples of the alkyl group include linear or branched alkyl groups such as methyl, ethyl, propyl, methylpropyl, butyl, isobutyl, tert-butyl, pentyl, and hexyl.
[0062] P3HA preferably contains 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, further more preferably 90 mol% or more, and further preferably 95 mol% or more of the 3-hydroxyalkanoate repeating unit represented by the general formula (1) relative to all monomer repeating units (100 mol%), and may be composed of 100 mol% of the 3-hydroxyalkanoate repeating unit represented by the general formula (1). In addition to the 3-hydroxyalkanoate repeating unit represented by the general formula (1), P3HA may contain, for example, a 4-hydroxyalkanoate repeating unit as another repeating unit.
[0063] In view of excellent marine decomposability, P3HA preferably contains 50 mol% or more of R represented by the general formula (1) relative to all monomer repeating units (100 mol%). 1 The 3-hydroxyalkanoate repeating unit containing a methyl group, i.e., the 3-hydroxybutyric acid (also referred to as 3-hydroxybutyrate, hereinafter also referred to as "3HB") repeating unit, preferably contains 70 mol% or more, further preferably contains 80 mol% or more, further preferably contains 90 mol% or more, and further preferably contains 95 mol% or more, which can be composed of 100 mol% of R represented by the general formula (1): 1It is composed of 3-hydroxyalkanoate repeating units with a methyl group. Specifically, for example, poly (3-hydroxybutyrate) (also called "P3HB"), poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (also called "P3HB3HV"), poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) (also called "P3HB3HH"), poly (3-hydroxybutyrate-co-3-hydroxyvalerate-co-3-hydroxyhexanoate) (also called "P3HB3HV3HH"), poly (3-hydroxybutyrate-co-4-hydroxybutyrate) (also called "P3HB4HB"), poly (3-hydroxybutyrate-co-3-hydroxyoctanoate), and poly (3-hydroxybutyrate-co-3-hydroxydecanoate) and the like can be cited. From the viewpoint of marine decomposition, the 3HB constituting P3HA is preferably all R-body (D-body). From the viewpoint of mechanical properties, P3HB3HH and / or P3HB4HB are preferred, and P3HB3HH is more preferred.
[0064] The composition ratio of the repeating units (monomer structural units) of P3HB3HH is not particularly limited, but from the viewpoint of the balance between flexibility and strength, the molar ratio of 3-hydroxybutyrate / 3-hydroxyhexanoate is preferably 99 / 1 to 80 / 20, more preferably 97 / 3 to 85 / 15. P3HB3HH may be used alone or in the form of a mixture of two or more P3HB3HHs having different composition percentages of 3HB.
[0065] In this specification, the composition ratio of the monomers in P3HA can be measured as follows. 2 mL of a sulfuric acid-methanol mixed solution (volume ratio, sulfuric acid: methanol = 15:85) and 2 mL of chloroform are added to about 20 mg of a sample and sealed, and heated at 100°C for 140 minutes to obtain a methyl ester of a polyester decomposition product. After cooling, 1.5 g of sodium bicarbonate is gradually added thereto for neutralization, and the mixture is left to stand until the generation of carbon dioxide gas stops. 4 mL of diisopropyl ether is added and mixed thoroughly, and then centrifuged. The composition of the hydroxyalkanoic acid methyl ester of the polyester decomposition product in the supernatant is analyzed by capillary gas chromatography to determine the composition ratio (monomer ratio) of the monomer units of P3HA.
[0066] P3HA is not particularly limited and can be manufactured by a known method. From the viewpoint of easily obtaining P3HA with high marine decomposability, it is preferably manufactured by a microbial manufacturing method. The microbial manufacturing method can use a known method. As long as the microorganism has the ability to produce P3HA, it is not particularly limited. As microorganisms with the ability to produce P3HA, for example, Aeromonas caviae, Cupriavidusnecator, Ralstonia eutropha, and Alcaligenes latus can be cited. In addition, in order to improve the productivity of P3HA, the Alcaligenes eutrophus AC32 strain (Alcaligenes eutrophus AC32, FERM BP-6038) (J. Bateriol., 179, p4821-4830 (1997)) into which the gene of the synthase group of poly (3-hydroxyalkanoate) is introduced can be used. Moreover, as P3HA, commercially available products such as biodegradable polymer GP (Green Planet (registered trademark)) manufactured by Kaneka Corporation can also be used.
[0067] The weight average molecular weight of P3HA is not particularly limited, but is preferably 50,000 to 3,000,000, and more preferably 100,000 to 1,500,000 from the viewpoint of moldability and strength. In this specification, the weight average molecular weight is a value measured by polystyrene conversion molecular weight distribution using gel permeation chromatography (GPC) using chloroform eluent. As a column in the GPC, any column suitable for measuring the above molecular weight can be used.
[0068] The melt flow rate (MFR) of P3HA is not particularly limited, and the melt flow rate (MFR) measured under the conditions of a temperature of 165°C and a load of 5 kg (49 N) according to JIS K 7210-1:2014 is preferably 0.1 to 100 g / 10 minutes, more preferably 1 to 50 g / 10 minutes, and further preferably 10 to 40 g / 10 minutes. When the melt flow rate is within the above range, the fluidity of the molten resin is within an appropriate range, and fiberization becomes good.
[0069] In addition to P3HA, P3HA fibers may also contain a crystal nucleating agent and / or a lubricant. In addition, in one or more embodiments of the present invention, in addition to P3HA, P3HA fibers may also contain other resin components and other additive components within the scope that does not hinder the effect of the present invention. For example, from the perspective of productivity and fiber properties, P3HA fibers preferably contain 0.05 to 12 parts by weight of a crystal nucleating agent, more preferably 0.1 to 10 parts by weight, further preferably 0.5 to 8 parts by weight, and particularly preferably 1 to 5 parts by weight, relative to 100 parts by weight of P3HA. In addition, from the perspective of productivity, P3HA fibers preferably contain 0.05 to 12 parts by weight of a lubricant, more preferably 0.1 to 10 parts by weight, further preferably 0.5 to 8 parts by weight, and particularly preferably 1 to 5 parts by weight, relative to 100 parts by weight of P3HA. In addition, P3HA fibers may contain other additive components of less than 5 parts by weight, less than 3 parts by weight, or less than 1 part by weight, relative to 100 parts by weight of P3HA. Furthermore, the P3HA-based fibers may contain 20 wt % or less, 10 wt % or less, or 5 wt % or less of other resin components relative to the total amount (100 wt %) of P3HA and other resin components.
[0070] P3HA fibers, for example, can be composed of a resin composition containing P3HA. That is, P3HA fibers can be obtained by fiberizing a resin composition containing P3HA. The above-mentioned resin composition is not particularly limited, and preferably contains more than 80% by weight of P3HA, more preferably more than 85% by weight, and further preferably more than 90% by weight. On the other hand, the upper limit can be 100% by weight, for example, less than 98% by weight or less than 95% by weight. By setting the content of P3HA to more than 80% by weight, there is a tendency for the biodegradability and marine decomposability of the pile cloth to be further improved.
[0071] The resin composition is not particularly limited, and from the viewpoint of productivity and fiber properties, it is further preferred to include a crystal nucleating agent. As a crystal nucleating agent, it is not particularly limited as long as it is a compound that has the effect of promoting the crystallization of P3HA. For example, from the viewpoint of improving the crystallization rate and containing in the fiber, it is preferably a sugar alcohol compound, polyvinyl alcohol, chitin and chitosan, more preferably a sugar alcohol compound, and more preferably pentaerythritol. The crystal nucleating agent can be used alone or in combination of two or more.
[0072] The content of the crystal nucleating agent in the resin composition is not particularly limited, and is preferably 0.05 to 12 parts by weight, more preferably 0.1 to 10 parts by weight, further preferably 0.5 to 8 parts by weight, and particularly preferably 1 to 5 parts by weight, relative to 100 parts by weight of P3HA. By setting the content of the crystal nucleating agent to 0.05 parts by weight or more, the crystallization promoting effect is improved, and there is a tendency to improve the productivity of the fiber. In addition, by setting the content of the crystal nucleating agent to 12 parts by weight or less, it is easy to suppress the decrease in viscosity during processing, the decrease in fiber properties, etc. while maintaining a sufficient crystallization rate promoting effect.
[0073] The resin composition is not particularly limited, but preferably further contains a lubricant from the viewpoint of productivity. The lubricant is not particularly limited as long as it is a compound that has the effect of imparting lubricity to P3HA. Examples thereof include fatty acid amides, alkylene fatty acid amides, glycerol monofatty acid esters, organic acid monoglycerides, sorbitan fatty acid esters, polyglycerol fatty acid esters, and higher alcohol fatty acid esters.
[0074] Among the above lubricants, compounds having the effect of imparting external lubricity are particularly preferred, and fatty acid amides and glycerol fatty acid esters are particularly preferred. As fatty acid amides, monoamides and bisamides of fatty acids can be cited. For the fatty acid (fatty acid part) constituting the fatty acid amide, from the viewpoint of the moderately high melting point of the resin composition and the suppression of the decrease in processability during melt processing, the number of carbon atoms is preferably 12 to 30, and the number of carbon atoms is more preferably 18 to 22. As fatty acid amides, specifically, behenic acid amide, erucic acid amide, palmitic acid amide, oleic acid amide, stearic acid amide, methylene bisstearic acid amide, ethylene bisstearic acid amide, ethylene bisoleic acid amide, and ethylene biserucic acid amide can be cited. As glycerol fatty acid esters, for example, monoesters of glycerol, diesters of glycerol, and triesters of glycerol can be cited. As triesters of glycerol, for example, glycerol diacetyl monolaurate, glycerol diacetyl monooleate, glycerol diacetyl monostearate, glycerol diacetyl monocaprylate, and glycerol diacetyl monocaprate can be cited. The lubricants may be used alone or in combination of two or more.
[0075] The content of the lubricant in the resin composition is not particularly limited, and is preferably 0.05 to 12 parts by weight, more preferably 0.1 to 10 parts by weight, further preferably 0.5 to 8 parts by weight, and particularly preferably 1 to 5 parts by weight, relative to 100 parts by weight of P3HA. By setting the content of the lubricant to 0.05 parts by weight or more, the friction between the resin composition and the metal surface in the extruder and the spinning machine can be suppressed, the decomposition of P3HA due to shear heat can be suppressed, and it is also easy to prevent the fibers extruded from the nozzle from adhering to each other. In addition, by setting the content of the lubricant to 12 parts by weight or less, P3HA can be more efficiently melted in the extruder, as a result, the fiber breakage can be suppressed without making the fiber too hard, and the productivity can be further improved.
[0076] The resin composition may contain other additives such as plasticizers, inorganic fillers, organic fillers (cellulose, etc.), antioxidants, ultraviolet absorbers, colorants such as dyes and pigments, and antistatic agents as needed within the range that does not impair the effects of the present invention. Other additives may be used alone or in combination of two or more. The amount of other additives added may be 5 parts by weight or less, or 1 part by weight or less, relative to 100 parts by weight of P3HA.
[0077] The resin composition may contain resin components (other resin components) other than P3HA as needed within the range that does not hinder the effect of the present invention. As other resin components, biodegradable resins are preferred. As other biodegradable resins, for example, petroleum-derived resins such as polylactic acid, polycaprolactone, polybutylene adipate terephthalate, polybutylene succinate adipate and polybutylene succinate, and natural polymers such as starch and cellulose can be cited. Other resin components can be used alone or in combination of two or more. Relative to the total amount of the resin components (100% by weight), the content of other resin components is preferably less than 20% by weight, more preferably less than 10% by weight, and further preferably less than 5% by weight.
[0078] The P3HA-based fibers can be obtained, for example, by melt spinning the above-mentioned resin composition.
[0079] First, a granular resin composition obtained by melt-kneading the above-mentioned resin composition is melted using a melt extruder, and the molten resin composition is continuously extruded from a nozzle to form a fiber, thereby making a spun filament (undrawn filament). The melt spinning temperature is not particularly limited as long as it is above the melting point of the resin composition and below the thermal decomposition temperature. For example, when the melting point of the resin composition is set to Tm, it can be [Tm+5°C]~[Tm+40°C], or [Tm+10°C]~[Tm+30°C]. More specifically, it can be 145~180°C, 150~180°C or 150~170°C. By setting the melt spinning temperature to above 145°C, the resin composition can be fully dissolved, so it is easy to stabilize the spinning. In addition, by setting the spinning temperature to below 180°C, the thermal decomposition of P3HA is suppressed, and it is easy to stabilize the spinning, and there is a tendency for the physical properties of the obtained fiber to be further improved. In addition, the melt spinning temperature refers to the temperature in the highest temperature region among the temperatures applied during the period when the resin composition is formed into fibers.
[0080] In this specification, the glass transition temperature, crystallization temperature, melting point and thermal decomposition temperature of a resin or resin composition can be measured by differential scanning calorimetry using a differential scanning calorimeter (e.g., manufactured by TA Instruments, model "DSC25") in a measurement temperature range of 0 to 180°C, a heating rate of 10°C / min, and a cooling rate of 10°C / min. Specifically, the measurement can be performed as described in the examples.
[0081] In this specification, the glass transition temperature and melting point of the fiber can be measured by differential scanning calorimetry using a differential scanning calorimeter (e.g., manufactured by TA Instruments, model "DSC25") in a measurement temperature range of 0 to 180°C, a heating rate of 10°C / min, and a cooling rate of 10°C / min. Specifically, the measurement can be performed as described in the examples. It should be noted that the glass transition temperature and melting point of the fiber are equivalent to the melting point of the resin or resin composition constituting the fiber.
[0082] The resin composition is not particularly limited, but has a weight average molecular weight of preferably 50,000 to 3,000,000, more preferably 100,000 to 1,500,000, for example, from the viewpoint of moldability and fiber strength.
[0083] The ambient temperature when the molten resin composition is extruded from the spinning head is not particularly limited. When the glass transition temperature of the resin composition is set to Tg, it can be [Tg+5°C] to [Tg+50°C], or [Tg+10°C] to [Tg+40°C]. More specifically, for example, it can be appropriately adjusted within the range of 5 to 40°C. It is preferred to blow straightening air to the fibers (spun filaments) extruded from the spinning head. The straightening air is also called quench air, which has the effect of stabilizing the flow of the yarn. In addition, the spinning filaments can also be cooled by using a gas that has been cooled as a quench gas. The temperature of the quench gas is preferably 5 to 40°C, more preferably 10 to 30°C. When it is above 5°C, it is easy to suppress the generation of residual stress in the fiber. When it is below 40°C, the solidification of the resin becomes sufficient, and it is easy to suppress the adhesion of the fibers. The wind speed of the quench air is not particularly limited, for example, it is preferably 0.1 to 3.0 m / s. When it is 0.1 m / s or more, the rectifying effect is easily exhibited, and when it is 3.0 m / s or less, the quenching wind is not too strong, the yarns are not disordered, and the occurrence of sticking of fibers and yarn breakage can be suppressed.
[0084] Next, the spun filaments are stretched to obtain stretched filaments (multifilaments). By stretching, fibers of the target fineness can be obtained, and the strength of the fibers can be improved. Stretching is not particularly limited, and can be performed in a two-step spinning stretching method or a direct spinning stretching method. In the two-step spinning stretching method, stretching is performed after the spun filaments are wound up. In the direct spinning stretching method, spinning and stretching are performed continuously without winding up the spun filaments. In addition, the stretching process can be performed in multiple steps by a combination of multiple roller pairs, etc. The surface temperature and speed of multiple rollers can be the same or different. The stretching temperature, specifically the surface temperature of the rollers, is not particularly limited, and can be, for example, 30 to 100°C, or 40 to 90°C. The stretching ratio can be, for example, 1.5 to 20 times. When the stretching ratio is 1.5 times or more, the strength of the fiber can be further improved. Before stretching, an oil agent can be applied to the spun filaments as needed.
[0085] The tensile strength of the stretched filament is preferably 0.5 to 10 cN / dtex, more preferably 0.7 to 10 cN / dtex, and further preferably 1.0 to 10 cN / dtex. When the tensile strength of the stretched filament is within the above range, it is easy to impart crimp, and the hand feel and tensile strength of the pile fabric using the short fibers obtained by cutting after imparting crimp can be further improved. In this specification, the tensile strength of the stretched filament can be measured based on JIS L1013:2021.
[0086] Next, the stretched filaments can be curled to impart bulkiness. The curling process is not particularly limited and can be performed by known curling methods such as a gear curling method and a stuffing box method. Thus, the obtained P3HA-type fibers have curling, specifically mechanical curling. The stretched filaments can be preheated as needed before imparting curling. The stretched filaments (curled filaments) imparted with curling can be used directly as pile fibers. From the perspective of the productivity of pile fabrics, it is preferably made into short fibers cut into a given fiber length for use. That is, P3HA-type fibers can be long fibers (stretched filaments) or short fibers. By using P3HA-type short fibers with curling as pile fibers, it is possible to appropriately obtain fleece-like and poodle-like pile fabrics that have excellent skin touch and heat retention and are lightweight.
[0087] The fiber length of the P3HA-based short fibers is not particularly limited, but can be 20 to 176 mm, 25 to 138 mm, or 28 to 110 mm from the viewpoint of easily obtaining a pile fabric having a large pile height, for example, a pile height of 8 mm or more.
[0088] From the perspective of both the carding passability of the staple fiber and the soft feel of the pile fabric, the number of curls of the P3HA type fiber is preferably 5 to 25 / 25mm, more preferably 6 to 20 / 25mm, further preferably 7 to 18 / 25mm, and particularly preferably 8 to 17 / 25mm. The number of curls of the P3HA type fiber can be measured as follows. Using crimped yarn or staple fiber, the sample length is set to 30mm, and the number of curled mountains with a length of 25mm is counted under a microscope, and n=15 is set, and the averaged value is used as the number of curls per 25mm. It should be noted that when the fiber length of the staple fiber is less than 25mm, the number of curled mountains in the entire length can be counted under a microscope to obtain the number of curls, and then converted to the number of curls per 25mm.
[0089] In the curling process, it is preferred to preheat the stretched filaments at 60 to 120°C, and then use a stuffer box to impart curling under the condition of a stuffer box pressure of 0.001 to 0.1 MPa. The preheating of the stretched filaments may be, for example, a wet heat treatment or a dry heat treatment. The wet heat treatment may be performed, for example, by steam or the like. The dry heat treatment may be performed, for example, by a hot air oven, an electric heater, or the like. The preheating temperature of the stretched filaments is more preferably 60 to 110°C, further preferably 70 to 100°C, and further preferably 80 to 90°C. The stuffer box pressure is more preferably 0.001 to 0.08 MPa, further preferably 0.001 to 0.06 MPa, and further preferably 0.001 to 0.04 MPa.
[0090] From the viewpoint of hand feel, the single fiber fineness of P3HA-based fibers is preferably 0.1 to 100 dtex, more preferably 0.5 to 50 dtex, further preferably 1.0 to 25 dtex, and further preferably 1.0 to 15 dtex. In the present specification, the single fiber fineness of P3HA-based fibers can be measured by an automatic vibroscope method.
[0091] From the viewpoint of mechanical strength, the tensile strength of the P3HA-based staple fibers is preferably 0.3 to 6.0 cN / dtex, more preferably 0.5 to 6.0 cN / dtex, and even more preferably 1.0 to 6.0 cN / dtex. In the present specification, the tensile strength of the P3HA-based staple fibers can be measured in accordance with JIS L1015:2021.
[0092] The weight average molecular weight of the P3HA-based fibers is not particularly limited, but is, for example, preferably 50,000 to 3,000,000, more preferably 100,000 to 3,000,000, further preferably 100,000 to 1,500,000, and further preferably 100,000 to 500,000.
[0093] From the viewpoint of easily improving the temperature conditions in the manufacturing process of the pile fabric such as polishing, the softening point of the P3HA-based fiber is preferably 100°C or higher, more preferably 110°C or higher, and further preferably 120°C or higher. In addition, the upper limit of the softening point is not particularly limited, and for example, from the viewpoint of imparting good anti-linting properties, it may be 150°C or lower or 140°C or lower. In this specification, the softening point of the fiber can be specifically measured as described in the examples.
[0094] From the viewpoint of preventing fusion between fibers and obtaining a soft and good hand feel, the 100°C dry heat shrinkage of P3HA fibers is preferably 10.0 to 30.0%, and more preferably 12 to 20%. In the present specification, the 100°C dry heat shrinkage of P3HA fibers can be calculated as follows: when P3HA fibers are heat treated for 15 minutes in a dry hot gas atmosphere at 100°C without load, the fiber length of the P3HA fibers before and after the heat treatment is measured under a load of 100 mg / dtex, and the calculation is based on the following mathematical formula (1). In the following mathematical formula (1), L0 is the fiber length of the fiber before the heat treatment, and L1 is the fiber length of the fiber after the heat treatment. In the present specification, the 100°C dry heat shrinkage of P3HA fibers can be specifically measured as described in the examples.
[0095] 100℃ dry heat shrinkage (%) = [(L0-L1) / L0] × 100 (1)
[0096] (Ground yarn)
[0097] The ground yarn contains fibers having a higher softening point than the P3HA fibers. Thus, in the heat pressing treatment described later, at least a portion of the P3HA fibers present on the back side closer to the ground yarn can be easily melted, and the P3HA fibers raised on the surface of the ground tissue are not melted. In addition, in the heat pressing treatment described later, it is easy to maintain good softness without making the ground tissue too hard. As fibers having a higher softening point than the P3HA fibers, from the viewpoint of biodegradability, biodegradable, especially marine degradable fibers are preferred. As biodegradable biodegradable fibers, synthetic fibers containing aliphatic polyesters other than P3HA, natural fibers, and regenerated fibers can be used. As aliphatic polyesters other than P3HA, for example, polylactic acid can be cited. As natural fibers, natural cellulose fibers and natural animal fibers can be cited. As natural cellulose fibers, for example, cotton fibers, kapok fibers, flax fibers, hemp fibers, ramie fibers, jute fibers, Manila fibers, and kenaf fibers can be cited. As natural animal fibers, for example, wool fibers, mohair fibers, cashmere fibers, camel fibers, alpaca fibers, and angora fibers can be cited. As regenerated fibers, regenerated cellulose fibers such as rayon and regenerated protein fibers such as regenerated collagen fibers (for example, regenerated collagen fibers "Luxaire (registered trademark)" manufactured by Kaneka Co., Ltd.) can be cited. As ground yarns, for example, textile yarns containing one or more of these biodegradable fibers can be used, and rayon, wool, cotton fibers, and regenerated collagen fibers that do not have a softening point, or textile yarns containing one or more of these fibers can be appropriately used.
[0098] From the viewpoint of more effectively suppressing hair loss, in addition to fibers having a softening point higher than that of P3HA fibers, the yarn preferably also contains hot-melt fibers. When the total amount of fibers constituting the ground yarn is set to 100% by weight, the content of the hot-melt fibers can be 5% by weight or more or 10% by weight or more. As hot-melt fibers, fibers having a softening point lower than that of the above-mentioned poly(3-hydroxyalkanoate) fibers can be suitably used. For example, hot-melt polyester fibers, hot-melt nylon fibers, etc. can be preferably cited. As hot-melt fibers, P3HA fibers for pile fibers can be used. When fiber yarns containing cotton fibers and P3HA fibers are used as ground yarns, in the hot pressing process, the P3HA fibers from the pile fibers that are closer to the back side than the ground yarn are melt-bonded with the P3HA fibers constituting the ground yarn, which can more effectively prevent hair loss. Hot-melt fibers can be used alone or in combination of two or more. From the viewpoint of improving the softness of the pile fabric, the content of the thermally fusible fiber is preferably 50% by weight or less, more preferably 30% by weight or less, when the total amount of fibers constituting the ground yarn is 100% by weight.
[0099] (Pile cloth)
[0100] From the viewpoint of flexibility, the bending rigidity of the ground structure of the pile fabric is 1.00×10 -4 N·m 2 / m or less, preferably 3.00×10 -5 N·m 2 / m or less, more preferably 1.0×10 -5 N·m 2 / m or less, more preferably 9.00×10 - 6 N·m 2 It should be noted that, from the viewpoint of softness, the smaller the bending rigidity of the ground structure of the pile fabric, the better. The lower limit is not particularly limited. For example, from the viewpoint of operability during product sewing, it can be 5.00×10 - 6 N·m 2 In the present specification, the bending rigidity of the ground structure of the pile fabric is measured using the ground structure as a sample, and specifically, it can be measured as described in the examples.
[0101] For pile fabrics, from the viewpoint that pile fibers of the pile portion do not melt and have an excellent hand feel, when the pile fabric is heat-treated in a 140°C dry heat gas atmosphere for 15 minutes, the change rate of the length of the pile fibers before and after the heat treatment (hereinafter also referred to as 140°C dry heat shrinkage rate) is preferably 15.0 to 40.0%, more preferably 18.0 to 38.0%, and even more preferably 20.0 to 35.0%. In this specification, the 140°C dry heat shrinkage rate of the pile fabric can be specifically measured as described in the examples.
[0102] From the viewpoint of effectively suppressing lint loss, the lint loss of the pile fabric is preferably 0.60 g / m 2 Below, more preferably 0.50g / m 2 Below, more preferably 0.40g / m 2 Below, more preferably 0.30g / m 2 It should be noted that the lower limit of the lint loss of pile fabric is close to 0 g / m 2 More preferably, it can be 0.01g / m 2 In the present specification, the amount of hair loss can be specifically measured as described in the examples.
[0103] The pile fabric is not particularly limited, but from the viewpoint of lightness and heat retention, the weight per unit length (weight per unit area) is preferably 300 to 3500 g / m, more preferably 300 to 2000 g / m, and further preferably 300 to 1200 g / m. In this specification, the weight per unit length of the pile fabric can be measured as described in the examples.
[0104] The pile height of the pile fabric is not particularly limited and can be appropriately set according to the application, and can be, for example, 2 to 120 mm. From the viewpoint of being suitably used as a fabric for clothing, it is preferably 2 to 70 mm, and more preferably 5 to 60 mm.
[0105] The pile fabric can be suitably used as eco-fur, and specifically, can be used for fabrics for clothing such as jackets and coats, fabrics for toys such as stuffed dolls, blankets, and bedding products such as bed sheets.
[0106] The pile fabric may be a pile fabric or a pile knitted fabric. When used as a grey fabric for clothing, a pile knitted fabric is preferred from the viewpoints of softness, bulkiness, heat retention, breathability, and drape. From the viewpoints of softness, bulkiness, and heat retention, the pile knitted fabric may be wool-like or curly-like. The pile knitted fabric may be a high pile knitted fabric with a pile height of 15 to 100 mm.
[0107] In a pile knitted fabric, the ground structure may be a knitted ground structure. More specifically, the pile knitted fabric includes a knitted ground structure and pile fibers that are entangled with the ground yarn constituting the ground structure and are raised on the surface of the above-mentioned ground structure. In the case of a pile knitted fabric, since the ground structure is a knitted structure, it is possible to form a structure with excellent elasticity. Knitting is usually performed by making a loop of one or more threads and hooking them on the loop to make the next new loop, and continuing this operation to sequentially make the loops continuous in a plane to form a fabric. Moreover, knitting that moves in the horizontal direction by making loops of the thread while reciprocating left and right to form a flat fabric, or by moving in a spiral shape to form a tubular fabric, etc. is called weft knitting, and knitting that forms a fabric by making loops of a plurality of neatly arranged warp yarns (warp yarns) while connecting adjacent left and right warp yarns through loops is called warp knitting. In addition, weft knitting includes plain knitting, rib knitting and double reverse knitting, and warp knitting includes plain weave knitting, warp pile weave, warp satin weave weave and chain weave weave. As a weaving method for the ground weave of pile knitted fabric, weft knitting is preferred from the viewpoints of commerciality and productivity.
[0108] In a pile knitted fabric, the arrangement of the pile fibers relative to the knitting of the ground structure may be such that the pile fibers are entangled in all the loops of the knitted ground yarn constituting the ground structure, or may be such that each loop of the knitted ground yarn has a portion in which the pile fibers are not entangled in the longitudinal direction and / or the horizontal direction.
[0109] Hereinafter, pile fabrics according to one or more embodiments of the present invention will be described with reference to the drawings. Figure 1 1 is a schematic diagram of an example of a pile fabric. The pile fabric 1 is composed of a ground yarn 2 and pile fibers 4, and the pile fibers 4 are wound around the ground yarn 2 (loops of the ground yarn) and opened on the surface of the ground structure to form a pile portion 3. In addition, on the back side of the pile fabric 1, outside the ground yarn 2, at least a part of the pile fibers 4 are fused to form a fusion bonded portion 5, which is pressed against the ground yarn 2.
[0110] (Method for producing pile fabric)
[0111] In one or more embodiments of the present invention, the method for manufacturing pile fabric may include, for example, a step of making the pile fabric and a step of heat-compression bonding the pile fabric from the back side of the ground structure. The pile fabric may be manufactured by a generally known method except for using the ground yarn and pile fibers described above.
[0112] The heat pressing treatment is performed under the temperature conditions that satisfy the following requirements: (1) the softening point of the poly(3-hydroxyalkanoate)-based fiber is higher than the melting point of the poly(3-hydroxyalkanoate)-based fiber + 10°C or lower, and (2) the softening point is lower than the softening point of the fiber in the ground yarn that is higher than the poly(3-hydroxyalkanoate)-based fiber. As a result, at least a portion of the P3HA-based fibers that are present on the back side of the ground yarn among the pile fibers wound around the ground yarn can be melted, and the P3HA-based fibers that are raised on the surface of the ground structure are not melted, thereby preventing the hair from falling off, and improving the feel of the pile and the softness of the ground structure. When the temperature during the heat pressing treatment is higher than the softening point of the poly(3-hydroxyalkanoate)-based fiber, at least a portion of the P3HA-based fibers that are present on the back side of the ground yarn can be melted. When the temperature during the heat press treatment is less than the melting point of the poly(3-hydroxyalkanoate)-based fibers + 10°C, the pile fibers entangled with the ground yarn in addition to the pile fibers on the back of the pile fabric can be prevented from melting, and the ground structure can be prevented from becoming hard. When the temperature during the heat press treatment is lower than the softening point of the fibers in the ground yarn that are higher than the softening point of the poly(3-hydroxyalkanoate)-based fibers, the P3HA-based fibers raised on the surface of the ground structure will not melt.
[0113] The temperature conditions in the hot pressing treatment are preferably above the softening point of the poly(3-hydroxyalkanoate) fiber + 5°C and below the melting point of the poly(3-hydroxyalkanoate) fiber, and more preferably above the softening point of the poly(3-hydroxyalkanoate) fiber + 5°C and below the melting point of the poly(3-hydroxyalkanoate) fiber -10°C.
[0114] The heat pressing treatment can be performed, for example, by placing the velvet cloth so that its back side contacts a heating roller or a heating plate, and applying pressure using a rubber roller or the like. When a heating roller or a heating plate is used, the heat pressing treatment can be performed for a short time, and at least a portion of the pile fibers (poly(3-hydroxyalkanoate) fibers) arranged on the back side of the ground tissue and located closer to the outside than the ground yarn can be heat pressed. Furthermore, since the pile fibers (poly(3-hydroxyalkanoate) fibers) on the surface of the velvet cloth are not heated to such an extent that they melt, the pile fibers standing up on the surface of the ground tissue will not melt. As the heating roller, a metal roller coated with a fluororesin such as polytetrafluoroethylene can be used.
[0115] It is preferred that the pile fiber side of the pile fabric with raised hair on the surface be cooled when and / or after the pile fabric is subjected to the heat pressing treatment from the back side. In addition, it is preferred that the back side of the pile fabric be cooled after the pile fabric is subjected to the heat pressing treatment from the back side. As the cooling method, it is preferred that the surface and / or back side of the pile fabric be cooled by a cooling roller through which water having a temperature of 50°C or less is circulated. From the viewpoint of cooling efficiency and productivity, the water temperature of the water circulated by the cooling roller is preferably 10 to 40°C, more preferably 10 to 35°C, and further preferably 15 to 30°C. When such cooling is performed, the dimensional stability of the pile fabric is high, and thermal damage to the pile fibers can be reduced.
[0116] Hereinafter, an example of the thermal compression bonding process will be described in more detail with reference to the drawings.
[0117] Figure 2 1 is a manufacturing process diagram schematically showing a process of performing a heat-compression bonding process on a pile fabric at a given temperature from the back side. The processing device 10 used for the heat-compression bonding process includes: a heating roller 11, a cooling rubber roller 12 that presses the heating roller 11 and circulates water below 50°C inside, a metal cooling roller 13 that presses the cooling rubber roller 12 and circulates water below 50°C inside, a metal cooling roller 14 that circulates water below 50°C inside, and a guide roller 15. A pile fabric raw material roll 18 is led out from a container 16 and supplied in a manner such that the back side 18b contacts the heating roller 11 and the surface (pile head side) 18a contacts the cooling rubber roller 12. In addition, after the heat-compression bonding process is performed, the back side 18b is cooled by the metal cooling roller 14. The pile fabric 19 after the processing is completed is stored in a container 17.
[0118] Thermocompression bonding is not limited to Figure 2 The processing device shown can also be used to Figure 2 The processing apparatus shown is partially constructed by a modified apparatus, hot plate and other apparatuses. For example, a rubber roller without cooling effect may be used instead of the cooling rubber roller 12, and the metal cooling roller 13 may be omitted.
[0119] In the thermal compression treatment, the pressure applied is preferably 0.01 to 100 Kgf / cm2 in terms of clamping pressure. 2 (0.98KPa~9.8MPa), the feeding speed of the pile fabric raw material roll is 0.1~20m / min, and the contact time of the heater (heating roller, etc.) is 1~60 seconds. In addition, from the viewpoint of reducing the damage to the surface of the pile fabric, the pressure is more preferably 2.0~80Kgf / cm in terms of clamping pressure. 2 (0.20~7.84MPa), heater contact time is 1~10 seconds.
[0120] In the case of pile knitted fabrics such as high pile knitted fabrics, since the high pile knitted fabric shrinks in the wale direction during the hot pressing treatment, it can be stretched in the wale direction after the hot pressing treatment. Such stretching treatment can be performed using a well-known device such as a tenter. A tenter is usually used to widen the fabric to a given width and perform heat setting while heating the fabric at a given temperature while holding the two ears of the fabric, but in this specification, as described above, heating may or may not be performed. In addition, in the tenter, as a method of holding the ears of the fabric, there are a cloth clip tenter method and a pin plate tenter method, and either method can be used. From the perspective of process stability and / or productivity, the pin plate tenter method is preferably used.
[0121] When the high pile knitted fabric is heated and stretched after the heat compression treatment, it is preferably carried out at the minimum necessary temperature and the minimum necessary air volume in order not to damage the surface of the high pile knitted fabric. For example, during the stretching treatment, the temperature is preferably 0°C or higher and below the softening point of the poly(3-hydroxyalkanoate) type fiber, more preferably 10°C or higher and below the softening point of the poly(3-hydroxyalkanoate) type fiber -10°C, and further preferably 20°C or higher and below the softening point of the poly(3-hydroxyalkanoate) type fiber -20°C.
[0122] The stretching treatment may be performed before the thermocompression bonding treatment. The stretching treatment before the thermocompression bonding treatment may be performed at room temperature (5 to 35°C).
[0123] In order to arrange the pile fabric neatly, the pile fibers raised on the surface of the ground structure can be polished before and / or after the hot pressing treatment. It should be noted that the polishing before the hot pressing treatment is also called pre-polishing. Although polishing is not necessarily required, in the case of polishing, the polishing needs to be performed at a temperature above the glass transition temperature of the poly(3-hydroxyalkanoate) fiber and below the softening point of the poly(3-hydroxyalkanoate) fiber -40°C. In this way, the soft feel of the pile portion can be maintained without causing the P3HA fibers raised on the surface of the ground structure to melt. Polishing is preferably carried out at a temperature of 30°C or higher than the glass transition temperature of the poly(3-hydroxyalkanoate) fibers and 40°C or lower than the softening point of the poly(3-hydroxyalkanoate) fibers, more preferably at a temperature of 35°C or higher than the glass transition temperature of the poly(3-hydroxyalkanoate) fibers and 45°C or lower than the softening point of the poly(3-hydroxyalkanoate) fibers, and further preferably at a temperature of 40°C or higher than the glass transition temperature of the poly(3-hydroxyalkanoate) fibers and 50°C or lower than the softening point of the poly(3-hydroxyalkanoate) fibers.
[0124] After the polishing treatment after the hot pressing treatment, a roller treatment may be performed within the range that does not hinder the purpose of the present invention. By performing the roller treatment, the fibers can be collected into bundles and curled to obtain so-called sheepskin-like or fleece-like products. The roller treatment can be performed, for example, at a temperature above the glass transition temperature and below the softening point of the poly(3-hydroxyalkanoate) fibers. In addition, it is preferably performed at a temperature above 30°C and below -10°C, the softening point of the poly(3-hydroxyalkanoate) fibers, and more preferably at a temperature above 60°C and below -20°C, the softening point of the poly(3-hydroxyalkanoate) fibers.
[0125] Pile fabrics and clothing made of the same will biodegrade if placed in an environment where microorganisms exist after use, so they do not require special disposal and are friendly to the global environment.
[0126] Example
[0127] Hereinafter, one or more embodiments of the present invention will be described in more detail based on examples. It should be noted that the present invention is not limited to these examples.
[0128] The measuring methods and evaluation methods used in Examples and Comparative Examples are as follows.
[0129] (Fiber properties)
[0130] (1) Single fiber fineness
[0131] Specifically, 20 fibers were randomly selected from the drawn filaments or staple fibers, and the fiber fineness was measured using an automatic vibration fineness measuring device "DENIER COMPUTER DC-11" (manufactured by Search Co., Ltd.), and the average was used as the single fiber fineness.
[0132] (2) Tensile strength
[0133] The tensile strength of the staple fibers was measured based on JIS L1015: 2021. Specifically, 20 fibers were randomly selected from the staple fibers, and for each fiber, a tensile measuring device Autograph AG-I (manufactured by Shimadzu Corporation) was used to measure the load at the time of cutting under the conditions of a tensile speed of 20 mm / min, a clamping interval of 20 mm, and a load cell with a rated capacity of 5 N, and the loads were averaged to obtain the tensile strength.
[0134] (3) 100℃ dry heat shrinkage
[0135] The fibers were heat treated for 15 minutes in a dry hot gas atmosphere at 100°C without load using a thermomechanical analyzer (TMA, manufactured by Hitachi High-Technologies Corporation, model "TMA / SS6100"). The fiber lengths before and after the heat treatment were measured under a load of 100 mg / dtex, and the 100°C dry heat shrinkage was calculated based on the following mathematical formula (1). In the following mathematical formula (1), L0 is the fiber length of the fiber before the heat treatment, and L1 is the fiber length of the fiber after the heat treatment.
[0136] 100℃ dry heat shrinkage (%) = [(L0-L1) / L0] × 100 (1)
[0137] (4) Softening point
[0138] 1g of fiber was opened and placed on a heating plate heated to any temperature with a pressure of 0.07Kgf / cm 2 When the pressure is applied for 3 seconds, the single fibers on the surface in contact with the heating plate soften and combine, and the temperature at which the fibers become a plate is defined as the softening point of the fibers.
[0139] (5) Glass transition temperature and melting point
[0140] The glass transition temperature and melting point of the fiber were measured by differential scanning calorimetry using a differential scanning calorimeter (manufactured by TA Instruments, model "DSC25") at a measurement temperature range of 0 to 180°C, a heating rate of 10°C / min, and a cooling rate of 10°C / min.
[0141] (Pile fabric properties)
[0142] (1) Weight per unit area
[0143] Samples cut into 30 cm x 30 cm squares were collected from the pile fabric, and n was set to 5. The weight of each sample was measured, and the average value was set to w (g). The weight per unit area W (g / m) of the pile fabric was calculated by the following mathematical formula.
[0144] W(g / m)=w×16.67
[0145] (2) Pile height
[0146] Place the pile fabric on a level table and arrange the pile fibers by hand. Figure 1 As shown in FIG. 1 , the distance 8 from the uppermost portion 6 of the ground structure to the uppermost portion 7 of the pile fibers was measured with a ruler. The average value of the measurements at any five locations was taken as the pile height of the pile fabric.
[0147] (3) Bending rigidity
[0148] The pile fabric was cut into 5 cm x 5 cm squares, and the pile fiber part was cut from the root with scissors to prepare a sample consisting only of the ground structure part. The sample was placed in a KBS-FB2 pure bending tester (manufactured by KATO TECH) and bent at a curvature of 2.5 cm. -1 The B value (bending hardness) was measured under the conditions of N = 2, and the average value was taken as the bending rigidity (N·m 2 / m).
[0149] (4) Softness
[0150] (a) The pile fabric was cut into pieces with a width of 20 mm in the longitudinal direction to obtain a fabric piece with a length of 200 mm and a width of 20 mm.
[0151] (b) If Figure 3 As shown, a fleece fabric sheet 21 is placed on a horizontal table 22 (600 mm in width and 600 mm in length) made of melamine resin. Next, the fleece fabric sheet 21 is gradually slid from the horizontal table 22 to the outside of the horizontal table 22 along the pile arrangement direction of the fleece fabric.
[0152] (c) Figure 4 As shown, the fleece fabric sheet 21 is slid until the angle a between the tangent line 31 and the horizontal stage 22 reaches 90°. The tangent line 31 is a tangent line drawn from the front end of the fleece fabric sheet 21 extending outward from the horizontal stage 22 .
[0153] (d) The distance L (90° distance) that the fleece fabric sheet 21 slid from the horizontal stand 22 was measured, and the softness was evaluated according to the following criteria.
[0154] A: 90° distance is less than 50mm (the pile fabric is very soft)
[0155] B: 90° distance is 50 mm or more and 55 mm or less (pile fabric is soft)
[0156] C: 90° distance greater than 55mm (pile fabric is hard; unqualified)
[0157] (5) Hair loss
[0158] A rubber brush (trade name "Prescale mat" 5 mm (particle diameter), 4 cm in length, 10.5 cm in width, manufactured by Fujifilm Corporation) was used while applying a load of 600 g (14.3 kg / cm 2 ) with a constant load, rub 10 times in the forward direction of the bristle arrangement with a stroke width of 30 cm, and rub 10 times in the reverse direction, collect the bristles with tape, and convert the weight into 10 ... 2 The corresponding weight is used as the amount of hair loss.
[0159] (6) Hair loss evaluation
[0160] Based on the amount of hair loss, hair loss evaluation was performed on a 4-level scale as described below.
[0161] A: 0.3g / m 2 Below (very good level)
[0162] B: more than 0.3g / m 2 And 0.6g / m 2 Below (good level)
[0163] C: more than 0.6g / m 2 And 1.0g / m 2 Below (slightly poor level)
[0164] D: more than 1.0g / m 2 (Bad Level)
[0165] (7) Melt-bonding of hair tips
[0166] The pile fabric was placed on a horizontal table, and the fusion bonding of the pile tips was confirmed by visual observation and touch.
[0167] No fusion: No fusion was observed by visual observation, and the tips of the pile fibers were independent. When the surface of the fabric was touched, no fusion was observed at the tips of the fibers, and the fabric felt smooth. Figure 5 This is a photograph showing the surface of the pile portion of an example of a pile cloth in which the pile tips are not fused.
[0168] There is fusion bonding: Fusion bonding is confirmed by visual observation, and the tips of multiple pile fibers in the pile head are fused together. When the surface of the fabric is touched by hand, fusion bonding of the tips of the pile fibers can be confirmed, and the fusion bonding part has a rough touch. Figure 6 This is a photograph showing the surface of the pile portion of a pile cloth in which an example of fusion of pile tips is observed.
[0169] (8) 140℃ dry heat shrinkage
[0170] Cut a 5cm x 5cm square sample from the fleece fabric and mark the back of the sample with a marker. Place the marked sample on a horizontal table. Figure 7As shown, the upper part 41 of the pile fiber 4 at the marked part is clamped with tweezers, and while stretching to eliminate the slack of the pile part 3, the distance 51 from the uppermost part 6 of the ground structure to the frontmost end 9 of the pile fiber is measured. This distance is taken as the length L2 of the pile fiber before heat treatment. Next, the sample piece is heat treated for 15 minutes in a dry hot gas atmosphere at 140°C without load. The length L3 of the pile fiber at the marked part after heat treatment is measured in the same manner, and the 140°C dry heat shrinkage is calculated based on the following mathematical formula (2). Assuming n=5, the averaged value is taken as the 140°C dry heat shrinkage (%) of the pile fabric.
[0171] 140℃ dry heat shrinkage (%) = [(L2-L3) / L2] × 100 (2)
[0172] (9) Feel
[0173] The feel was evaluated on a 4-level scale as described below.
[0174] A: The pile fibers on the surface of the ground fabric are not fused and are at the same level as pile fabrics that have not been heat treated.
[0175] B: Slightly inferior to grade A, but the raised pile fibers on the surface of the ground fabric are not fused, which is a level that does not cause any practical problems.
[0176] C: Slightly rough and hard, problematic for practical use (unqualified)
[0177] D: Extremely rough and hard, not practical (unqualified)
[0178] In the examples and comparative examples, the following fibers were used.
[0179] (Pile Fiber)
[0180] Pile fibers 1: P3HB3HH short fibers of Production Example 1 described later were used.
[0181] (Ground yarn)
[0182] Ground yarn 1: Two cotton yarns with a cotton count of 40 are combined and used. Cotton yarn has no softening point.
[0183] Ground yarn 2: Two spun yarns with a cotton count of 30 were prepared by blending cotton fibers having a fiber length of 28.6 to 34.1 mm and P3HB3HH fibers of Production Example 1 described below at a ratio of 50 parts by weight:50 parts by weight. Cotton fibers have no softening point.
[0184] (Production Example 1)
[0185] 100 parts by weight of a copolymer resin (manufactured by Kaneka Co., Ltd.) having a molar composition ratio of 3HB units / 3HH units of P3HB3HH of 94 / 6, Mw of 350,000, and MFR (165°C, 5kg) of 12 g / 10 minutes, 1.0 parts by weight of pentaerythritol (manufactured by Nippon Synthetic Chemical Co., Ltd., "Neulizer P") as a crystal nucleating agent, and 0.5 parts by weight of erucic acid amide and 0.5 parts by weight of behenic acid amide as lubricants were dry-blended, and the mixture was melt-kneaded and pelletized at 150°C using an extruder to obtain a pelletized resin composition. The obtained pelletized resin composition had a glass transition temperature of 2°C, a crystallization temperature of 100°C, a melting point of 146°C, a thermal decomposition temperature of 180°C, and a weight average molecular weight of 350,000. It should be noted that the glass transition temperature, crystallization temperature, melting point and thermal decomposition temperature of the pelletized resin composition were measured by differential scanning calorimetry using a differential scanning calorimeter (manufactured by TA Instruments, model "DSC25") in a measurement temperature range of 0 to 180°C, a heating rate of 10°C / min, and a cooling rate of 10°C / min. The weight average molecular weight of the pelletized resin composition was measured by gel permeation chromatography (GPC) using a chloroform eluent through a polystyrene-converted molecular weight distribution.
[0186] The obtained resin composition (pellets) was melted by a kneading extruder (single screw extruder, screw diameter 25 mm). The obtained melt was ejected from a spinning nozzle (temperature: 175°C, shape of the ejection hole: circular, diameter of the ejection hole: 0.3 mm, number of ejection holes: 368) to obtain spun filaments. The flow rate of the melt was adjusted to 12.2 kg / h by a gear pump. Next, in the spinning cylinder, 20°C air was blown at a speed of 0.7 m / s to the spun filaments ejected from the circumferential direction.
[0187] The cooled spun filaments were extracted by the first extraction roller (speed: 448 m / min), transported sequentially by the first to fourth transport rollers (speed: 471 m / min), and then wound up by the first winding roller (speed: 461 m / min) and stored at room temperature (5 to 35°C) for 18 hours.
[0188] Next, the spun filaments (unstretched filaments) were extracted from the first winding roller section by the second extraction roller section (speed: 50 m / min, roller temperature: 30°C), stretched by the stretching roller section (110 m / min, roller temperature: 90°C), transported by the take-off roll section (heat treatment roller section) (speed: 110 m / min, roller temperature: 100°C), and wound by the second winding roller section (speed: 100 m / min), thereby obtaining the stretched filaments. The stretching ratio was set to 2.0 times. It should be noted that as the extraction roller section and the conveying roller section, roller sections each consisting of two rollers of the same speed and the same temperature were used.
[0189] The drawn filaments were combined into a suitable fineness, preheated to 100°C with steam, and then fed to a stuffer box at a conveying speed of 8.7 m / min and a nip pressure of 2.0 kg / cm 2 , the filling pressure was 0.04 MPa, and the crimped yarn was cut into a fiber length of 51 mm using a tow cutter, thereby obtaining P3HB3HH short fibers. The single fiber fineness of the obtained P3HB3HH short fibers was 6.0 dtex, the tensile strength was 1.51 cN / dtex, the 100°C dry heat shrinkage was 15.3%, the glass transition temperature was 2°C, the melting point was 146°C, the softening point was 125°C, and the weight average molecular weight was 250,000.
[0190] (Example 1)
[0191] A sliver knitting machine (circular loom) for making eco-friendly fur was used. The circular loom was supplied with pile fiber slivers (10-14 g / m) formed by ground yarn 1 and P3HB3HH short fibers of manufacturing example 1, and a high pile knitted fabric was knitted. The number of loops in the vertical rows of the ground structure was 16-17 per inch, and the number of loops in the horizontal rows was 22-33 per inch. Next, the pile fibers on the raised surface of the high pile knitted fabric were arranged by pre-polishing and pre-shearing. Specifically, pre-polishing was performed twice at 80°C, followed by pre-shearing twice. Then, a pin-plate tenter dryer was used to stretch the width of the high pile knitted fabric from 140 cm to 160 cm while the temperature in the dryer was at room temperature (5-35°C).
[0192] For the high pile knitted fabric (width 160 cm) obtained above, use Figure 2 The heat pressing device shown in the figure has a heating roller temperature of 130°C, a contact time between the heating roller and the high pile knitted fabric of 5 seconds, and a clamping pressure between the heating roller and the cooling rubber roller of 50 Kgf / cm 2The high pile knitted fabric was then subjected to heat compression bonding from the back side under the condition of (4.9 MPa). At this time, the width of the grey fabric of the high pile knitted fabric was shrunk to 135 cm. Then, the high pile knitted fabric was dried for 3 minutes using a pin tenter dryer at a temperature of 70°C in the dryer while stretching the width to 160 cm, and then cooled to below 50°C while maintaining the width at 160 cm.
[0193] The obtained high pile knitted fabric was polished, brushed and sheared to trim the pile fibers on the surface of the pile fabric. Specifically, brushing was performed twice, then polished twice at 80°C, then sheared twice, and finally polished once at 80°C. Finally, a wool-like high pile knitted fabric with a unit weight of 800 g / m and a pile height of 18 mm was obtained.
[0194] (Example 2)
[0195] A wool-like high-pile knitted fabric having a basis weight of 800 g / m and a pile height of 18 mm was obtained in the same manner as in Example 1 except that the temperature of the heating roller was set to 140°C during the thermal compression bonding treatment.
[0196] (Example 3)
[0197] A wool-like high-pile knitted fabric having a basis weight of 800 g / m and a pile height of 18 mm was obtained in the same manner as in Example 1 except that the temperature of the heating roller was set to 150° C. during the thermocompression bonding treatment.
[0198] (Example 4)
[0199] The high pile knitted fabric obtained in the same manner as in Example 1 was further subjected to a tumble treatment for 15 minutes in a tumble dryer heated to 110° C., thereby obtaining a high pile knitted fabric having a basis weight of 800 g / m and a pile height of 15 mm.
[0200] (Example 5)
[0201] A wool-like high-pile knitted fabric having a basis weight of 800 g / m and a pile height of 18 mm was obtained in the same manner as in Example 1 except that the polishing was not performed.
[0202] (Example 6)
[0203] A wool-like high-pile knitted fabric having a basis weight of 800 g / m and a pile height of 18 mm was obtained in the same manner as in Example 1 except that the above-mentioned ground yarn 2 (cotton-P3HB3HH blended yarn) was used as the ground yarn.
[0204] (Comparative Example 1)
[0205] A wool-like high-pile knitted fabric having a basis weight of 800 g / m and a pile height of 18 mm was obtained in the same manner as in Example 1 except that the temperature of the heating roller was set to 120°C during the thermal compression bonding treatment.
[0206] (Comparative Example 2)
[0207] A wool-like high-pile knitted fabric having a basis weight of 800 g / m and a pile height of 18 mm was obtained in the same manner as in Example 1 except that the temperature of the heating roller was set to 160° C. during the thermal compression bonding treatment.
[0208] (Comparative Example 3)
[0209] When the pile fibers on the surface of the pile cloth were arranged by polishing, brushing and shearing after the hot pressing treatment, the brushing was first performed twice, then polished three times at 90°C, then sheared twice, and finally polished twice at 90°C. Except for this, a wool-like high pile knitted fabric with a unit area weight of 800 g / m2 and a pile height of 18 mm was obtained in the same manner as in Example 3.
[0210] (Comparative Example 4)
[0211] When the pile fibers on the surface of the pile cloth were arranged by polishing, brushing and shearing after the hot pressing treatment, the pile fibers were first brushed twice, then polished three times at 110°C, then sheared twice, and finally polished twice at 110°C. In the same manner as in Example 3, a wool-like high pile knitted fabric with a unit area weight of 800 g / m2 and a pile height of 18 mm was obtained.
[0212] (Comparative Example 5)
[0213] As an anti-linting treatment for the pile fabric, a backing treatment was performed instead of the hot pressing treatment. In the same manner as in Example 1, a wool-like high pile knitted fabric with a unit area weight of 800 g / m and a pile height of 18 mm was obtained. The backing treatment method is as follows. After the pre-shearing and pre-polishing are completed, the back side of the obtained pile fabric is impregnated with a backing resin. The backing resin uses an emulsified copolymer latex with an acrylic acid ester as the main component, and is prepared into an aqueous solution (emulsion) with a latex concentration of 40 wt%, and is impregnated with 50 g / m at a resin solid content concentration. 2 Then, the high pile knitted fabric was dried for 3 minutes using a pin tenter dryer at a temperature of 130° C. in the dryer while being stretched to a width of 160 cm, and then cooled to 80° C. or less while maintaining the width at 160 cm.
[0214] The manufacturing conditions of the pile fabrics of the examples and comparative examples are shown in the following Table 1. The softness, lint loss, lint loss evaluation, fuzz fusion, 140°C dry heat shrinkage and hand feel of the pile fabrics of the examples and comparative examples, and the bending rigidity of the ground structure of the pile fabrics were measured and evaluated as described above, and the results are shown in the following Table 2.
[0215] [Table 1]
[0216]
[0217] a: Temperature of the tenter frame after backing treatment
[0218] b: Time of tenter frame treatment after backing treatment
[0219] c: Polishing temperature before backing treatment
[0220] d: Temperature of polishing after backing treatment
[0221] [Table 2]
[0222]
[0223] The evaluations of softness, linting and hand feel of the pile fabrics of Examples 1 to 6 were all A to B, satisfying the properties required of pile fabrics. Among them, the linting evaluation of Example 6 using cotton-P3HB3HH blended yarn as the ground yarn was A, which was a particularly excellent linting property.
[0224] On the other hand, in Comparative Example 1, in which the temperature of the heating roller during the thermocompression bonding process was set to 120°C, the pile fibers on the back side of the pile fabric were not fused, and the evaluation of linting was D. In addition, in Comparative Example 2, in which the temperature of the heating roller during the thermocompression bonding process was set to 160°C, the bending rigidity of the ground structure was greater than 1.00×10 -4 In addition to the pile fibers on the back of the pile fabric, the pile fibers wrapped around the ground yarn also melted, making the ground structure hard, and the softness of the pile fabric was evaluated as C. In addition, for the pile fabrics of Comparative Example 3 polished at 90°C and Comparative Example 4 polished at 110°C, the tips of the hairs melted, and the hand feeling was evaluated as D. For the pile fabric of Comparative Example 5 that was subjected to a backing treatment at a tenter temperature of 130°C instead of a thermocompression treatment, the fibers at the pile portion shrank and melted, and the hand feeling was evaluated as D.
[0225] The present invention is not particularly limited, and may include the following embodiments.
[0226] [1] A pile fabric comprising a ground fabric and pile fibers entangled with ground yarns constituting the ground fabric and raised on a surface of the ground fabric,
[0227] The pile fibers include poly(3-hydroxyalkanoate) fibers.
[0228] The ground yarn comprises fibers having a higher softening point than the poly(3-hydroxyalkanoate)-based fibers.
[0229] Among the pile fibers entangled with the ground yarn, at least a portion of the poly(3-hydroxyalkanoate)-based fibers present on the back side of the ground yarn are melt-bonded.
[0230] When the pile fabric was heat-treated for 15 minutes in a dry hot gas atmosphere at 140° C. without a load, the change rate of the pile fiber length before and after the heat treatment was 15.0 to 40.0%.
[0231] The bending rigidity of the ground structure of the pile fabric is 1.00×10 -4 N·m 2 / m or less.
[0232] [2] The pile fabric according to [1], wherein the fibers having a softening point higher than that of the poly(3-hydroxyalkanoate)-based fibers contained in the ground yarn include biodegradable fibers.
[0233] [3] The pile fabric according to [2], wherein the biodegradable fiber includes one or more fibers selected from the group consisting of natural cellulose fibers, natural animal fibers, and regenerated cellulose fibers.
[0234] [4] The pile fabric according to any one of [1] to [3], wherein the ground yarn further includes thermally fusible fibers, and the softening point of the thermally fusible fibers is lower than or equal to the softening point of the poly(3-hydroxyalkanoate)-based fibers.
[0235] [5] The pile fabric according to [2] or [3], wherein the ground yarn contains one or more fibers selected from cotton fibers, rayon fibers, wool fibers, and regenerated collagen fibers as biodegradable fibers.
[0236] [6] The pile fabric according to [5], wherein the ground yarn further includes poly (3-hydroxyalkanoate)-based fibers as thermally fusible fibers.
[0237] [7] The pile fabric according to any one of [1] to [6], which is a pile knitted fabric.
[0238] [8] The pile fabric according to any one of [1] to [7], wherein the pile height is 8 mm or more.
[0239] [9] The pile fabric according to [4], wherein the thermally fusible fibers include poly (3-hydroxyalkanoate)-based fibers.
[0240]
[10] A method for manufacturing a pile fabric, the method comprising:
[0241] A process for manufacturing a pile fabric including a ground fabric and pile fibers entangled with a ground yarn constituting the ground fabric and raised on a surface of the ground fabric; and
[0242] The step of subjecting the pile fabric to a heat-compression bonding treatment from the back side,
[0243] The pile fibers include poly(3-hydroxyalkanoate) fibers.
[0244] The ground yarn comprises fibers having a higher softening point than the poly(3-hydroxyalkanoate)-based fibers.
[0245] The temperature conditions for the heat-compression bonding treatment are: (1) above the softening point of the poly(3-hydroxyalkanoate)-based fibers and below the melting point of the poly(3-hydroxyalkanoate)-based fibers + 10°C; and (2) below the softening point of the fibers in the ground yarn that have a softening point higher than the poly(3-hydroxyalkanoate)-based fibers.
[0246] The method does not include the step of polishing the pile fibers raised on the surface of the above-mentioned ground structure; or in the case of including the step of polishing the pile fibers raised on the surface of the above-mentioned ground structure, the polishing is carried out at a temperature above the glass transition temperature of the above-mentioned poly(3-hydroxyalkanoate) fibers and below the softening point of the above-mentioned poly(3-hydroxyalkanoate) fibers -40°C.
[0247]
[11] The method for producing a pile fabric according to
[10] , comprising:
[0248] A step of polishing the pile fibers raised on the surface of the ground structure.
[0249]
[12] The method for producing a pile fabric according to
[10] or
[11] , wherein the polishing is performed before the heat-pressing treatment and / or after the heat-pressing treatment.
[0250]
[13] The method for producing a pile fabric according to any one of
[10] to
[12] , wherein the fibers having a softening point higher than that of the poly(3-hydroxyalkanoate)-based fibers contained in the ground yarn include biodegradable fibers.
[0251]
[14] The method for producing a pile fabric according to any one of
[10] to
[13] , wherein the ground yarn further includes a thermally fusible fiber, and the softening point of the thermally fusible fiber is lower than the softening point of the poly (3-hydroxyalkanoate) type fiber.
[0252]
[15] The method for producing pile fabric according to
[13] , wherein the ground yarn contains one or more fibers selected from cotton fiber, rayon, wool and regenerated collagen fiber as biodegradable fibers.
[0253]
[16] The method for producing a pile fabric according to
[15] , wherein the ground yarn further contains poly (3-hydroxyalkanoate)-based fibers as the thermally fusible fibers.
[0254]
[17] The method for producing a pile fabric according to
[14] , wherein the thermally fusible fibers include poly (3-hydroxyalkanoate) fibers.
[0255]
[18] The method for producing a pile fabric according to any one of
[10] to
[17] , which is a pile knitted fabric.
Claims
1. A pile fabric comprising a ground fabric, and pile fibers entangled with ground yarns constituting the ground fabric and raised on a surface of the ground fabric, The pile fibers include poly(3-hydroxyalkanoate) fibers. The ground yarn comprises fibers having a higher softening point than the poly(3-hydroxyalkanoate)-based fibers. Among the pile fibers entangled with the ground yarn, at least a portion of the poly(3-hydroxyalkanoate)-based fibers present on the back side of the ground yarn are melt-bonded. When the pile fabric was heat-treated for 15 minutes in a dry hot gas atmosphere at 140° C. without a load, the change rate of the pile fiber length before and after the heat treatment was 15.0 to 40.0%. The bending rigidity of the ground structure of the pile fabric is 1.00×10 -4 N·m 2 / m or less.
2. The pile fabric according to claim 1, wherein The fibers having a softening point higher than that of the poly(3-hydroxyalkanoate)-based fibers contained in the ground yarn include biodegradable fibers.
3. The pile fabric according to claim 2, wherein The biodegradable fibers include at least one type of fibers selected from natural cellulose fibers, natural animal fibers, and regenerated cellulose fibers.
4. The pile fabric according to claim 1 or 2, wherein The ground yarn further includes thermally fusible fibers, and the softening point of the thermally fusible fibers is lower than the softening point of the poly(3-hydroxyalkanoate)-based fibers.
5. The pile fabric according to claim 2, wherein The ground yarn contains one or more fibers selected from cotton fiber, rayon, wool and regenerated collagen fiber as biodegradable fibers.
6. The pile fabric according to claim 5, wherein The ground yarn further includes poly(3-hydroxyalkanoate)-based fibers as thermally fusible fibers.
7. The pile fabric according to claim 1 or 2, which is a pile knitted fabric. 8 . The pile fabric according to claim 1 , wherein the pile height is 8 mm or more.
9. A method for manufacturing a pile cloth, the method comprising: A process for manufacturing a pile fabric including a ground fabric and pile fibers entangled with a ground yarn constituting the ground fabric and raised on a surface of the ground fabric; and The step of subjecting the pile fabric to a heat-compression bonding treatment from the back side, The pile fibers include poly(3-hydroxyalkanoate) fibers. The ground yarn comprises fibers having a higher softening point than the poly(3-hydroxyalkanoate)-based fibers. The temperature conditions for the heat-compression bonding treatment are: (1) above the softening point of the poly(3-hydroxyalkanoate)-based fibers and below the melting point of the poly(3-hydroxyalkanoate)-based fibers + 10°C; and (2) below the softening point of the fibers in the ground yarn that have a softening point higher than the poly(3-hydroxyalkanoate)-based fibers. The method does not include the step of polishing the pile fibers raised on the surface of the above-mentioned ground structure; or when the method includes the step of polishing the pile fibers raised on the surface of the above-mentioned ground structure, the polishing is carried out at a temperature above the glass transition temperature of the above-mentioned poly(3-hydroxyalkanoate) fibers and below the softening point of the above-mentioned poly(3-hydroxyalkanoate) fibers -40°C.
10. The method for manufacturing a pile fabric according to claim 9, comprising: A step of polishing the pile fibers raised on the surface of the ground structure.
11. The method for producing a pile fabric according to claim 9 or 10, wherein: The above-mentioned polishing is performed before the heat-pressing treatment and / or after the heat-pressing treatment.
12. The method for producing a pile fabric according to claim 9 or 10, wherein: The fibers having a softening point higher than that of the poly(3-hydroxyalkanoate)-based fibers contained in the ground yarn include biodegradable fibers.
13. The method for producing a pile fabric according to claim 9 or 10, wherein: The ground yarn further includes thermally fusible fibers, and the softening point of the thermally fusible fibers is lower than the softening point of the poly(3-hydroxyalkanoate)-based fibers.
14. The method for producing a pile fabric according to claim 12, wherein: The ground yarn contains one or more fibers selected from cotton fiber, rayon, wool and regenerated collagen fiber as biodegradable fibers.
15. The method for producing a pile fabric according to claim 14, wherein: The ground yarn further includes poly(3-hydroxyalkanoate)-based fibers as thermally fusible fibers.
16. The method for producing a pile fabric according to claim 9 or 10, wherein the pile fabric is a knitted pile fabric.
Citation Information
Patent Citations
Pile woven and knitted fabrics
JP2002004151A
Biodegradable carpet
JP2002248047A
Pile fabric and process for producing same
WO2011055455A1